Differential pre- and postsynaptic modulation of chemical transmission in the squid giant synapse by tyrosine phosphorylation - Llinás, Rodolfo (The National Academy of Sciences of the USA, 1997)
To assess the role of tyrosine phosphorylation/dephosphorylation balance in synaptic transmission, a set of studies was implemented at the squid giant synapse. Presynaptic induction of tyrosine phosphorylation, following administration of the tyrosine phosphatase inhibitor pervanadate, produced a sizable increase in presynaptic calcium current and a concomitant and paradoxical decrement of the postsynaptic potential amplitude. Presynaptic microinjection of an active protein tyrosine kinase dramatically increased calcium currents and incremented postsynaptic potential amplitude. By contrast, the same procedure at the postsynaptic terminal reduced the size of the postsynaptic potential. This differential effect may be prodromic to long-term plasticity, as postsynaptic sensitivity is momentarily deemphasized, whereas presynaptic second messenger cascades triggered by increased calcium currents are accentuated.